Characterization of motion modes of pseudo-two dimensional granular materials in a vertical rotating drum. (August 2016) - Yulia,; Mardiansyah, Y; Khotimah, S N; Suprijadi,; Viridi, S
Abstract: The aim of this work is to characterize the modes of motion of pseudo-two dimensional granular materials in a vertical rotating drum. The granular materials are 4 mm diameter marbles, which are put in a flat drum with 16 cm diameter and 5 mm thickness. Rotation axis of the drum is always perpendicular to the direction of gravity. Granular materials in a vertical rotating drum usually have six modes of motion i.e. slipping, slumping, rolling, cascading, cataracting, and centrifuging. Those modes depend on number of granular particles, rotation speed, and types of materials of granular particles. Characterization of modes of motion in this work has been conducted by varying number of particles, rotation speed, and types of materials. Rotation speed is varied from 15 rpm to 125 rpm, while number of granular material is varied from 50 to 600. Each steel and plastic granular materials has five modes of motion with centrifuging mode is absence in observation of steel materials and slipping mode is absence in observation of plastic materials, both for the same parameter ranges used in the experiments. Parameters room of number of particles against rotation speed for both types of materials are presented.